PENGARUH PROMOSI JABATAN TERHADAP MOTIVASI KERJA APARATUR SIPIL NEGARA DI KANTOR BUPATI KABUPATEN GOWA - Minhajri, Minhajri; Hakim, Lukman; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACTThis study aims to determine the development of the state civil apparatus in improving the quality of work of employees at the Department of Population and Civil Registration of North Luwu Regency. This type of research is qualitative by using descriptive type. Collecting data through observation, interviews and documentation. The results of this study indicate that the implementation of bureaucratic responsiveness in the Population and Civil Registry Office of Enrekang Regency can be said to have been implemented well, this is in accordance with data showing that the implementation of bureaucratic responsiveness in the Regency Population and Civil Registry Office Enrekang is in the high category. There is an important aspect that needs to be considered, namely the aspect of placing service users as customers whose interests must always be prioritized. Keywords: Job promotion, work motivation